2009
DOI: 10.1177/1049731509335531
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving Fidelity in the National Evidence-Based Practices Project

Abstract: Background: The National Evidence-Based Practices (EBPs) Project developed and tested a model for facilitating the implementation of five psychosocial EBPs for adults with severe mental illness in the United States. Methods: The implementation model was tested in 53 sites in 8 states. In each site, one of the five EBPs was adopted for implementation and then studied for a 2-year period using a combination of qualitative and quantitative methods. Findings: At baseline, none of the sites had programs attaining h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 62 publications
(66 reference statements)
9
135
0
1
Order By: Relevance
“…The fit of IMR within extant program structures may also explain the relative passivity of leadership support necessary to implement IMR. However, it is important to note FACTORS AFFECTING IMR IMPLEMENTATION 16 that structural changes not commonly observed in the current study-namely IMR-specific supervision and adapting policies, procedures, and documentation-were found to affect IMR fidelity and quality in previous studies (Bartholomew & Kensler, 2010;Bond et al, 2009;Rychener et al, 2009), rather than adoption. Practically nothing is known regarding the fidelity of IMR within VHA and these factors may still prove relevant to fidelity.…”
Section: Factors Affecting Imr Implementation 14mentioning
confidence: 56%
See 1 more Smart Citation
“…The fit of IMR within extant program structures may also explain the relative passivity of leadership support necessary to implement IMR. However, it is important to note FACTORS AFFECTING IMR IMPLEMENTATION 16 that structural changes not commonly observed in the current study-namely IMR-specific supervision and adapting policies, procedures, and documentation-were found to affect IMR fidelity and quality in previous studies (Bartholomew & Kensler, 2010;Bond et al, 2009;Rychener et al, 2009), rather than adoption. Practically nothing is known regarding the fidelity of IMR within VHA and these factors may still prove relevant to fidelity.…”
Section: Factors Affecting Imr Implementation 14mentioning
confidence: 56%
“…Despite IMR's effectiveness, IMR implementation can vary widely. In the National Implementing Evidence-based Practices (EBPs) Project, only half of the programs providing IMR reached "successful" levels of fidelity (Bond, Drake, McHugo, Rapp, & Whitley, 2009) and subsequent multi-site studies showed substantial variation in fidelity (Hasson-Ohayon, Roe, & Kravetz, 2007;Salyers, Godfrey, et al, 2009). Importantly, higher program fidelity was associated with better consumer outcomes in one trial (Hasson-Ohayon et al, 2007).…”
Section: Illness Management and Recoverymentioning
confidence: 99%
“…The opposite end of the intensity spectrum is characterized by wraparound case management, usually in the form of ACT (Stein & Test, 1980). ACT offers an unlimited number of contacts between the individual substance abuser and a multidisciplinary team of professionals (Bond, Drake, McHugo, Rapp, & Whitley, 2009). Services may be provided directly by the ACT team or by referral to other resources.…”
Section: Practice Modelsmentioning
confidence: 99%
“…Therefore mental health practitioners need to be creative and culturally sensitive when helping service users in exploring and identifying the strengths and virtue of characters within themselves and the wider environment. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w Bond, Drake, McHugo, Rapp, & Whitley, 2009;McHugo et al, 2007;Whitley, Gingerich, Lutz, & Mueser, 2009). ...…”
Section: Applying Strengths-based Practices Cross-culturallymentioning
confidence: 99%
“…Strengths-based, recovery-oriented approaches are increasingly relevant to and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w Bond, Drake, McHugo, Rapp, & Whitley, 2009;McHugo et al, 2007;Whitley, Gingerich, Lutz, & Mueser, 2009). Existing research provides little evidence-based guidelines on the best approaches to training staff in strengths-based approaches.…”
Section: Directions For Policy Future Research and Service Provisionmentioning
confidence: 99%